Efficacy And Safety Of Sodium-Glucose Cotransporter-2 (Sglt2) And Dipeptidyl Peptidase-4 (DPP-4) Inhibitor Combination Therapy In Patients With Type 2 Diabetes Inadequately Controlled By Metformin - Kumar, Darshan; Bhatty, Shaheen; Syed Muhammad Kashif; Pawan Kumar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the effectiveness and safety of combining SGLT2 inhibitors with or without DPP4 inhibitors as an add-on therapy for type 2 diabetes patients. Study Design: Quasi-Experimental Study Place and Duration of Study: Dr. Ruth KM Pfau Civil Hospital and Dow University Hospital Ojha Campus, Dow University of Health Sciences, Karachi, Pakistan, from Mar 21 to Dec 23. Methodology: The study assessed type 2 diabetes patients on Metformin alone with an HbA1c level exceeding 7% and evaluated various clinical and biochemical markers. Results: In a study of 239 obese and poorly controlled diabetic patients, 58.58% were female, and 41.42% were male, with an age range of 40-60 years. Diabetes duration was below 5 years in 17.57% of patients, between 5 and 10 years in 44.45%, and over 10 years in 38.07%. The treatment groups were as follows: Metformin + SGLT2 inhibitors (27.00%), Metformin + DPP4 inhibitors (32.00%), and all three combinations (41.00%). During a span of 36 weeks, a significant difference was seen in the levels of HbA1c (p < 0.001). Moreover, the BMI of male subjects. In addition, there were significant decreases in FBS, RBS, and triglyceride levels, whereas creatinine levels did not change. Conclusion: Metformin, when combined with SGLT2 and DPP4 inhibitors, improves glycaemic control and weight reduction in morbid obesity patients, especially in males, with significant changes in HbA1c, fasting, and postprandial glucose levels.